2018
DOI: 10.1039/c8fo00730f
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin 3-O-glucoside prevents the development of maladaptive cardiac hypertrophy and diastolic heart dysfunction in 20-week-old spontaneously hypertensive rats

Abstract: The present study investigated the effects of cyanidin 3-O-glucoside (C3G) in cardiomyocytes (CM) and fibroblasts exposed to endothelin 1 (ET1), as well as in the spontaneously hypertensive rat (SHR) model, alone or in combination with hydrochlorothiazide (HCT). Adult rat CM and cardiac fibroblasts (CF) were pretreated with C3G and co-incubated with ET1 (10-7 M) for 24 hours. Five-week-old male SHR and their normotensive controls, Wistar-Kyoto rats (WKY), received one of 4 treatments via oral gavage daily for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
8
17
0
Order By: Relevance
“…The consumption of oats with beta-glucan (5.5 g per day) has been reported to reduce systolic BP by 7.5 mmHg and diastolic BP by 5.5 mmHg in patients diagnosed with mild or borderline hypertension (Keenan, Pins, Frazel, Moran, & Turnquist, 2002). In addition, previous study also showed that oat beta-glucan is beneficial in terms of reducing in body weight between SHR and WKY rats (at the end of the study) which is consistent with past studies (Aloud et al, 2018), (Dickhout & Lee, 1998). However, SHR has also been reported to weigh less than age and sex-matched WKY rats (Swislocki & Tsuzuki, 1993).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The consumption of oats with beta-glucan (5.5 g per day) has been reported to reduce systolic BP by 7.5 mmHg and diastolic BP by 5.5 mmHg in patients diagnosed with mild or borderline hypertension (Keenan, Pins, Frazel, Moran, & Turnquist, 2002). In addition, previous study also showed that oat beta-glucan is beneficial in terms of reducing in body weight between SHR and WKY rats (at the end of the study) which is consistent with past studies (Aloud et al, 2018), (Dickhout & Lee, 1998). However, SHR has also been reported to weigh less than age and sex-matched WKY rats (Swislocki & Tsuzuki, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…The current study showed that SHR had significantly increased level of MDA, a marker of oxidative stress. Our previous studies also reported that SHR exhibit higher level of oxidative stress related markers by 20 weeks of age (Aloud et al, 2018;Thandapilly et al, 2010). Beta-glucan alone and the combination of both beta-glucan and avenanthramide C were able to prevent elevation of MDA in SHR.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Both whole grape and red grape skin polyphenolic extract consumption reduced blood pressure, improved vascular function and compliance, and attenuated cardiac hypertrophy in the spontaneously hypertensive rat [ 208 , 209 ]. Treatment with cyanidin-3- O -β-glucoside for 15-week prevents cardiac hypertrophy and diastolic dysfunction but is unable to alleviate severe hypertension in spontaneously hypertensive rats, which means that cyanidin-3- O -β-glucoside may have direct cardioprotective effects independent of blood pressure [ 210 ]. This was confirmed by another study with obese C57BL/6 mice where, despite the fact that blueberries supplementation reduced both systolic and diastolic blood pressure, cyanidin-3- O -β-glucoside did not reduce blood pressure.…”
Section: Anthocyanins’ Health Effects On Cardiovascular and Neurodmentioning
confidence: 99%
“…Similarly, lycopene derived from tomato skins has been shown to reduce the expansion of interstitial fibrosis that occurs in rat models of myocardial infarction [ 24 ]. At a cellular level, resveratrol and cyanidin-3-glucoside have been shown to blunt fibroblast activation in vitro [ 25 , 26 ]. However, these approaches have not been effective yet clinically, potentially due to an inability to achieve an effective therapeutic dose in patients [ 27 ].…”
Section: Introductionmentioning
confidence: 99%